1986
DOI: 10.1002/1097-0142(19861001)58:7<1461::aid-cncr2820580714>3.0.co;2-d
|View full text |Cite
|
Sign up to set email alerts
|

Susceptibility to NK cell lysis is abolished in tumor cells by a factor which restores their contact inhibited growth

Abstract: It is well recognized that physical contact between natural killer (NK) cells and tumor targets is necessary for cell lysis. Therefore, any modulation of the tumor cell surface that alters intercellular contact could affect NK cell cytotoxicity. To examine this hypothesis, a contact inhibitory factor (CIF), which had been shown to restore contact inhibition of growth to several malignant cell lines was tested for its ability to render such cells immune to recognition by NK cells. When three NK-sensitive melano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

1987
1987
2008
2008

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…We believe this decrease in G 2 /M population of cells in the presence of hOGG1 is due to the protection this protein imparts to 2-MEinduced damage and not due to the regulation of hOGG1 itself, as it is well established that the hOGG1 gene is not regulated by cell cycle and is constitutively expressed (Dhenaut et al, 2000(Dhenaut et al, , 2001. Furthermore, cytotoxic effects of 2-ME studied by other groups showed an increase in LDH release (Nabi et al, 1986;Kachadourian et al, 2001), in this study we found that the presence of recombinant hOGG1 protects the cells from the cytotoxic effects of 2-ME based on our LDH data. Thus, our results show that 2-ME-induced damage to mtDNA may contribute to a decrease in cellular survival, induction of cell cycle arrest, mitochondrial membrane hyperpolarization and apoptosis via the Fas activation.…”
Section: Cytochrome C Cox Iisupporting
confidence: 62%
“…We believe this decrease in G 2 /M population of cells in the presence of hOGG1 is due to the protection this protein imparts to 2-MEinduced damage and not due to the regulation of hOGG1 itself, as it is well established that the hOGG1 gene is not regulated by cell cycle and is constitutively expressed (Dhenaut et al, 2000(Dhenaut et al, , 2001. Furthermore, cytotoxic effects of 2-ME studied by other groups showed an increase in LDH release (Nabi et al, 1986;Kachadourian et al, 2001), in this study we found that the presence of recombinant hOGG1 protects the cells from the cytotoxic effects of 2-ME based on our LDH data. Thus, our results show that 2-ME-induced damage to mtDNA may contribute to a decrease in cellular survival, induction of cell cycle arrest, mitochondrial membrane hyperpolarization and apoptosis via the Fas activation.…”
Section: Cytochrome C Cox Iisupporting
confidence: 62%
“…CIF, a diffusible substance found in the conditioned medium of revertant (contact-inhibited) hamster melanocytic cells (Lipkin and Knecht, 1974), mediates certain changes in morphology, growth and differentiation of various cultured tumor cells. Such alterations include: (a) restoration of contact inhibition, (b) regain of anchorage-and serum-dependent proliferation, (c) induction of pigment-cell differentiation antigens on mouse and hamster melanoma cells, and (d) reduced susceptibility of human melanoma, colon carcinoma, and erythroleukemia cells to lysis by NK cells Knecht, 1974, 1976;Lipkin et al, 1978Lipkin et al, , 1985Lipkin et al, , 1986Nabi et al., 1986). CIF reduces cell proliferation by initiating a GI arrest, or at least a prolongation of this cell-cycle phase (Lipkin and Knecht, 1976).…”
mentioning
confidence: 99%